Rekomendasi Reward Menggunakan Metode SAW Dengan Kode OTP Via Telegram Sebagai Pengamanan Login Menggunakan Algoritme SHA1 - Septian Apriyanto; Ahmad Pudoli; Dewi Kusumaningsih (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2021)
As a step to motivate employees to maximize billing and achieve the targets set by PT Telkom, the enterprise service division applies rewards once a month for employees who have the highest values for criteria such as absenteeism, honesty, loyalty and target achievement. So far, the assessment system for the monthly reward recipients is assessed and decided directly by the manager of the enterprise service division which is considered to lack transparency in providing values because employees do not know how much value the enterprise service manager gives to employees for each of the predetermined criteria, so it is still there are some employees who feel they are not being treated fairly because their performance is considered to be maximum but still have not received a reward from the company. In this web-based Decision Support System, the researcher applies the SAW method which is considered fair enough in providing calculations to draw the reward recipient's decision recommendations because each criterion will have a weighted value and normalization calculations whose divisors will be taken from the maximum value. In operating this application, a security system is also made at the login for the admin account which acts as a value giver, in order to avoid problems in the future if there are irresponsible parties who know the admin username and password and then change the value that has been given. The security system built uses a One Time Password (OTP) code which will be encrypted in the database using the SHA-1 algorithm, which will then be sent via the telegram chat application. From the results of the calculation of the sample data that has been carried out, it is found that the employee with the highest score was selected as the recipient of the reward with a value of 0.96879359983694 / 96.88%.